Online Preschool Education during The Covid-19 Pandemic: Teacher Experiences - Özer-Akkaya, Merve; Çam Aktaş, Bilge (Southeast Asia Early Childhood Journal, 2023)
Due to the global Covid 19 pandemic, face-to-face education was suspended, and distance education was adopted in all education levels. Various measures were implemented to ensure continuous education in the preschool level, where distance education was adopted for the first time in history. The present study aimed to determine the views and experiences of preschool teachers on distance education. The study was conducted with the phenomenology approach, a qualitative research method, and semi-structured online interviews were conducted with 9 preschool teachers, who were employed at schools that served various socioeconomic levels in different cities, using the developed interview form. The content analysis conducted in the study that preschool teachers had similar negative experiences such as problems associated with Internet connection and infrastructure during the distance education process, technology adaptation problems of low-income parents, low online class participation, and difficulties associated with fulfilling the individual needs of the children. Furthermore, teachers also had positive experiences such as higher parental participation, better recognition of the teacher’s role in education, integration of technology in education, e-content development, and professional development in distance education. Various measures should be adopted to ensure equality of opportunity in distance education based on the present study findings.